2017
DOI: 10.1002/lary.26559
|View full text |Cite
|
Sign up to set email alerts
|

Expanded transcanal transpromontorial approach to the internal auditory canal: Pilot clinical experience

Abstract: 4. Laryngoscope, 127:2608-2614, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 19 publications
0
40
0
Order By: Relevance
“…46 HRJBs can make endoscopic access to the IAC very difficult in certain cases, just like in other skull base approaches to the region. 21,30,34 We feel that the currently proposed classification can offer safer and more efficacious surgical planning to the described region. In Manjila and Semaan classification types 1 and 2, a transpetrous approach to the posterior fossa (translabyrinthine approach) provides adequate exposure given adequate skeletonization of the sigmoid sinus and dome of the jugular bulb is performed.…”
Section: Typementioning
confidence: 97%
“…46 HRJBs can make endoscopic access to the IAC very difficult in certain cases, just like in other skull base approaches to the region. 21,30,34 We feel that the currently proposed classification can offer safer and more efficacious surgical planning to the described region. In Manjila and Semaan classification types 1 and 2, a transpetrous approach to the posterior fossa (translabyrinthine approach) provides adequate exposure given adequate skeletonization of the sigmoid sinus and dome of the jugular bulb is performed.…”
Section: Typementioning
confidence: 97%
“…Marchioni et al (11) reported no CSF leakage after exclusive ETTA. In Presutti et al study (16), 1 of 10 patients underwent expanded ETTA experienced postoperative CSF otorhinorrhea, which completely resolved in the follow-up period. Wick et al (3) reported no postoperatively complication after ETTA on 4 patients with vestibular schwannomas.…”
Section: Discussionmentioning
confidence: 92%
“…The mean hospital stay was 2.8 days in this study. Presutti et al (16) concluded that expanded ETTA (using both endoscope and microscope, which allows bimanual dissection of the tumor and therefore, enhanced control of the surrounding neurovascular structures) was successful in the management of 10 patients with vestibular schwannoma Koos stage I or II with no facial dysfunction in the last follow-up. Marchioni et al (9) described the expanded ETTA for the successful resection of vestibular schwannoma in patients with Koos grade II and III with no complication and good facial nerve result and concluded that this technique was a new approach that combined the advantages of a microscopic technique with the ones offered by the endoscope.…”
Section: Discussionmentioning
confidence: 99%
“…A good pictorial view of the excavated mastoid segment of facial nerve through transcanal route was found in L. Presutti et al work. 9 Butthe details of such dissection were not mentioned there. In author's own previous work, the mastoid segment of facial nerve had also been exposed through the transcanal endoscopic mastoidectomy approach.…”
Section: Discussionmentioning
confidence: 99%